Haul as a Medium for Character Education: Building Local Wisdom through Kiai Tradition - Khoiriyah, Khoiriyah; Suteja, Jaja; Rintaningrum, Ratna; Ningrum, Dewi Aprilia; Aji, Yunita Abdullah (UIN Syarif Hidayatullah Jakarta, 2025)
Religious traditions are integral to character education and the preservation of cultural values. This study examines the haul (annual commemoration) of Abuya Uci in Pasar Kemis, Tangerang, as a medium for shaping religious character and preserving local cultural heritage. The annual event at Al-Istiqlaliyah Islamic Boarding School in Cilongok attracts tens of thousands of attendees, facilitating socio-religious interaction. The gap identified in this study is the lack of research on religious commemorations as tools for character education and cultural preservation. Using a library research approach, this study highlights how the haul of Kiai Uci transmits values like humility (tawadhu’), service (khidmah), love of knowledge, and social solidarity. The results suggest that the haul is more than a ritual; it serves as a hidden curriculum for character education and a strategic tool for preserving cultural heritage. It underscores the role of the kiai as a guardian of values, even posthumously.